Pembuatan tepung ikan di Kecamatan Galesong Utara Kabupaten Takalar - Jawina Saokani Sofyan; Indra Cahyono (Seminar Nasional Pengabdian Kepada Masyarakat, 2018)
The activity of making fish bone flour conducted atSampulungan Village, Galesong Utara Districts, for 6 month i.e. March – August 2018. The activity aim for solve and give solutions about production, marketing manajemen from KUB Cahaya Karmila dan KSU Turin. Economic approach and utilization of power are things that must be implemented by both cooperatives through the application of technology. There are several stages in the process of making fish bone flour i.e. the first clean fish bones from the rest of fish meat, and then steamed, and then put in the oven so that the water content decreases, and then pured with blender so be fish bone meal. Fish bone meal is very useful for animal feed because it contain calcium and cosmetic industries.